2013
DOI: 10.3389/fneur.2013.00167
|View full text |Cite
|
Sign up to set email alerts
|

Tau Oligomers as Potential Targets for Alzheimer’s Diagnosis and Novel Drugs

Abstract: A cumulative number of approaches have been carried out to elucidate the pathogenesis of Alzheimer’s disease (AD). Tangles formation has been identified as a major event involved in the neurodegenerative process, due to the conversion of either soluble peptides or oligomers into insoluble filaments. Most of recent studies share in common the observation that formation of tau oligomers and the subsequent pathological filaments arrays is a critical step in AD etiopathogenesis. Oligomeric tau species appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 49 publications
2
38
0
2
Order By: Relevance
“…There was no tau detected below the dimer/trimer bands (Fig.S1A and B). Guzman‐Martinez et al had demonstrated tau oligomers in the platelets of AD patients showing bands between 100 and 190 kDa molecular weights, which is in accordance with our observation 35. Tau aggregates at the dimer or trimer size range have also been observed in synaptosome‐enriched fraction from AD brains 36.…”
Section: Resultssupporting
confidence: 92%
“…There was no tau detected below the dimer/trimer bands (Fig.S1A and B). Guzman‐Martinez et al had demonstrated tau oligomers in the platelets of AD patients showing bands between 100 and 190 kDa molecular weights, which is in accordance with our observation 35. Tau aggregates at the dimer or trimer size range have also been observed in synaptosome‐enriched fraction from AD brains 36.…”
Section: Resultssupporting
confidence: 92%
“…Thus, both TNT1 and TOC1 are pretangle pathological tau changes in AD that may indicate potential toxic mechanisms of tau pathologies, and pS422 is an early change that is well correlated with cognitive decline. The hypothesis that the earliest modifications in tau drive its toxicity is consistent with accumulating evidence that the classical inclusions (such as NFTs) are not the toxic form of tau (32, 33), but rather it is the small, misfolded oligomeric species (29, 3437). …”
Section: Introductionsupporting
confidence: 60%
“…Tau is dissociated from microtubules when phosphorylated. In AD, tau becomes abnormally hyperphosphorylated by kinases such as cyclin-dependent kinase-5 (Cdk5), glycogen synthase kinase-3β (GSK-3β), dualspecificity tyrosine phosphorylated-regulated kinase 1A, Ca 2+ /calmodulin-activated protein kinase II, casein kinase I, and dual-specificity tyrosine phosphorylation regulated kinase 1A (DYRK1A) kinase (Ryoo et al, 2007;Farías et al, 2011;Guzmán-Martinez et al, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 98%